Hybrid Electrical System Optimization of Remote Island using HOMER - Mansur, Adrian (INTEK: Jurnal Penelitian, 2021)
Renewable energy is an important solution in improving access to electricity, especially in isolated areas including the utilization of solar power however intermittency is becoming the main challenge that is faced in the application of Solar Power Plant (SPP). Hybrid system implementation becomes a strategy in an effort to improve system reliability based on the variation in load and intermittency of SPP. Salemo Island is one of the areas that has utilized SPP as one of the sources of electricity energy, but its operation has not been optimal as the load increases, therefore, a study was conducted to optimize the hybrid electrical system based on the current existing conditions. The results of the study showed that with the addition of SPP capacity of 200 kWp and the addition of batteries as much as 120 units, it could obtained an optimal Leveled Cost Of Energy (LCOE) value of 1,306 IDR/kWh and operating costs of 450 million with a Net Present Cost (NPC) of 8.4 billion and a capital cost of 3.2 billion. Another option is the addition of SPP 150 kWp with a lower capital cost value of 2.02 Billion, but greater than the aspect of operating cost of 883 million and LCOE of 1,897 Rp/ kWh